Carrageenan molecule conformations and electrokinetic properties in electrolyte solutions: Modeling and experimental measurements. (December 2021) - Michna, Aneta; Płaziński, Wojciech; Lupa, Dawid; Wasilewska, Monika; Adamczyk, Zbigniew
Abstract: Physicochemical properties of κ–carrageenan (KC) molecules and their aqueous solutions were determined using molecular dynamics modeling and experimental techniques. Chain conformations, the end-to-end distance, the gyration radius and the density of the molecule were theoretically calculated. Experimentally, the diffusion coefficient and electrophoretic mobility of the molecules were measured for ionic strength range 10 −4 to 0.15 M and different pHs. Using these data, the hydrodynamic diameter, the electrokinetic charge and the effective ionization degree of KC molecules were determined. The dynamic viscosity measurements for dilute KC solutions enabled to determine of its molecule intrinsic viscosity for various ionic strengths. The viscosity attained 50, 000 for dilute electrolyte solutions compared to the Einstein value for spheres equal to 2.5. This confirmed that KC molecules assumed extended conformations in accordance with theoretical modeling. It is concluded that the application of complementary theoretical and experimental methods furnishes reliable information about KC molecule conformations in electrolyte solutions. Graphical abstract: Image 1 Highlights: Physicochemical properties of κ-carrageenan (KC) were thoroughly determined. The electrokinetic charge of KC molecules was determined. KC properties were adequately described by the slender body hydrodynamics. KC molecule thickening properties were predicted.